Environmentally responsive MRI contrast agents. - Davies, G; Kramberger, I; Davis, J (2013)
Biomedical imaging techniques can provide a vast amount of anatomical information, enabling diagnosis and the monitoring of disease and treatment profile. MRI uniquely offers convenient, non-invasive, high resolution tomographic imaging. A considerable amount of effort has been invested, across several decades, in the design of non toxic paramagnetic contrast agents capable of enhancing positive MRI signal contrast. Recently, focus has shifted towards the development of agents capable of specifically reporting on their local biochemical environment, where a switch in image contrast is triggered by a specific stimulus/biochemical variable. Such an ability would not only strengthen diagnosis but also provide unique disease-specific biochemical insight. This feature article focuses on recent progress in the development of MRI contrast switching with molecular, macromolecular and nanoparticle-based agents.